Peran Motivasi, Disiplin, dan Kompensasi dalam Meningkatkan Kinerja Pegawai PT PLN Bali - Asril, Akmil (Jurnal EMT KITA, 2024)
This research aims to examine the influence of motivation, work discipline and compensation on the performance of PT PLN employees in Bali Province. By focusing on the dynamics of the number of electricity customers, company organizational structure, and human resource performance, this research integrates these variables in a comprehensive thinking framework. The data analysis method uses multiple linear regression and hypothesis testing, with performance measurement involving aspects of quality, quantity, cooperation, initiative and reliability. The research results show that simultaneously motivation, work discipline, and compensation have a significant influence on employee performance. Partially, motivation and work discipline have a positive and significant influence on performance, while compensation is not significant. The coefficient of determination (R2) indicates that these factors can explain variations in employee performance of 68.1%. A partial analysis of compensation implies that the system may be based on employee skills and performance outcomes, while the assumption of employee well-being suggests that the level of compensation may not significantly influence performance. The research results show that there are factors that influence the performance of human resources in the electricity industry. The implications include improving human resource management policies, creating a more productive work environment, and improving the quality of employee performance to achieve company goals. These findings can be the basis for developing more effective management strategies at PT PLN in Bali Province.